Chengdu Reduplication: An Optimality Theoretic Analysis*. (October 2015) - Lin, Hui-shan
This paper examines four reduplication patterns in Chengdu that involve special tone sandhi (i.e. AA, AAB, ABB and AABB) and proposes an Optimality Theoretic (OT) analysis to account for the reduplicant size, the reduplicant placement, and tone sandhi of these patterns. For reduplicant size, the monosyllabic reduplicant size in AA, AAB, and ABB and the disyllabic size in AABB are shown to be governed by different alignment constraints that contribute to the variant reduplicant sizes. For reduplicant placements, it is shown that though the reduplicant in AABB appears to be infixal, it is actually a suffix (just as the other patterns), whose movement into the base is forced by a linearity constraint that requires the input segmental sequence to be preserved in the output. Finally, for tone sandhi, it is shown that the special tonal alternations in the four reduplication patterns are the combinational effect of general tone sandhi and a floating high tone, which usually docks on the left edge of the reduplicant.